CARDIOVASCULAR ADAPTATION TO PHYSICAL TRAINING - Akmarawita kadir (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2009)
The purpose of the exercise is to increase strength, endurance, flexibility, agility and speed. These powers relate to the structure and function in the body. If exercise is done regularly and in accordance with the way practice, it is expected that any changes (adaptations) that support the achievement of these forces.